Pengaruh Harga, Citra Merek, dan Celebrity Endorser Terhadap Keputusan Pembelian Produk Sepatu Futsal Specs: Studi Kasus pada Pengguna Sepatu Futsal Merek Specs di Kebumen - Sapdho Agil Saputra; Feby Evelyna (Jurnal Ilmiah Mahasiswa Manajemen, Bisnis dan Akuntansi (JIMMBA), 2022)
This study aims to examine and analyze the effect of price, brand image and celebrity endorser on purchasing decisions. This research was conducted on the people of Kebumen Regency, data collection was carried out through distributing questionnaires to 100 respondents who used the Specs brand futsal shoes. Data collection techniques by distributing questionnaires. The analysis used is validity test, reliability test, classical assumption test, multiple linear regression analysis test and coefficient of determination. The analysis technique used is the SPSS version 23 analysis program for Windows. The results obtained in this study indicate that partially the price, brand image and celebrity endorser variables have a significant effect on purchasing decisions. Simultaneously, price, brand image and celebrity endorser variables have a significant effect on purchasing decisions.